2022
DOI: 10.3390/molecules27092987
|View full text |Cite
|
Sign up to set email alerts
|

Insight of the Functional and Biological Activities of Coconut (Cocos nucifera L.) Protein by Proteomics Analysis and Protein-Based Bioinformatics

Abstract: Coconut (Cocos nucifera L.) is one of the most critical economic crops in the tropics and sub-tropics. Although coconut protein has attracted more and more attention due to its nutritional potential, the lack of proteomic information has limited its practical application. The present study aimed to investigate the coconut meat proteome by shotgun proteomics and protein-based bioinformatic analysis. A grand total of 1686 proteins were identified by searching the National Center for Biotechnology Information (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…They found at least 200 protein spots, and sequencing some of these proteins by MALDI-TOF-TOF-MS revealed homology to 7S globulin, glutelin and a putative receptor-like protein kinase. Recently, Ma et al [ 19 ], using shotgun protein sequencing of coconut solid endosperm, identified 1686 proteins. The in silico digestion of globulins and antioxidant proteins with pepsin and trypsin helped them to predict peptides with emulsifying and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…They found at least 200 protein spots, and sequencing some of these proteins by MALDI-TOF-TOF-MS revealed homology to 7S globulin, glutelin and a putative receptor-like protein kinase. Recently, Ma et al [ 19 ], using shotgun protein sequencing of coconut solid endosperm, identified 1686 proteins. The in silico digestion of globulins and antioxidant proteins with pepsin and trypsin helped them to predict peptides with emulsifying and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…Vicilin-like protein encodes a storage protein located in the chloroplast as well as cytoplasm (Van de Vondel et al, 2020) that is found in cereal seeds and nuts (Burrieza et al, 2019). Vicilin-like proteins play roles in seed growth and response to external stress (Ma et al, 2022). Vicilin-like protein is also necessary for LEA protein coding for seed germination that was provided by ABA (Hu & Ma, 2006).…”
Section: Related-homeobox 3 (Bhb3)mentioning
confidence: 99%